FINACIAL PERFORMANCE OF TAXI OPERATION IN BANDUNG - Syarif Munandar ( NIM : 269 97 030), Ari
Abstract: This study was carried out in Bandung, with two main objectives. The first objective was to identify the main characteristics taxi operation and to identify which factors influenced the vehicle operating costs. The second objective was to develop a multivariable cost allocation model, and to assess the financial performance of taxi operation before and after the 1997 monetary crisis. An attitude survey concluded that 57.65% of taxi passengers considered the operational speed was fair. 74.12% of taxi passengers considered the level of comfort was good, 79.41% considered that the level of safety was good, but only 51.76% thought that the taxis level of service was appropriate to the fare. An attitude survey of taxi drivers concluded that driver income in general was decreasing by 30.90% and that there was a reduction of 32.68% in the mean number of trips per day due to the monetary crisis. The significant factors that influenced a taxi s operating costs (for Gemah Ripah Taxi) were transport expenses, which constitute 47.07% of the total cost before the crisis (after crisis 47.03%) and maintenance and garage expenses about 32.66% (after crisis 36.45%). Other significant factors were administration and general expenses that constituted 20.27% (after crisis 16.520). With regard to standing and variable costs, there were increases of 14.18% and 38.86% for Gemah Ripah Taxi, 19.07% and 24.73% for Centris Taxi and 0.76% and 36.09% for Kota Kembang Taxi respectively. The vehicle operating cost model of a typical a taxi company in Bandung was validated as follows: C = 327.4H +78.6K +5,360,026.6v + 0.012 R (before crisis) C = 513.4H + 109.8K + 5,849,625.6 V + 0.015 R (after crisis) where C is annual cost of system operation (in rupiahs), H is annual vehicle-hours of service, K is annual vehicle-km of service, V is peak vehicle needs, and R is annual system revenue. The assessment of the financial performance found that this was decreasing after the crisis compared to before. Gemah Ripah Taxi s financial performance decreased from 1.185 to 1.021 (13.91% reduction), Centris Taxi from 1.063 to 1.009 (5.13% reduction) and Kota Kembang Taxi from 1.104 to 0.998 (9.56% reduction). While the financial performance of the Kostaba/4848 Taxi could only be estimated for the after crisis. This had the value of 1.014.